Adoption of joint village land use planning by the Government of Tanzania to increase tenure security for livestock keepers - CGIAR Research Program on Policies, Institutions, and Markets (2019)
From 2010-2019, ILRI and partners piloted joint village land use planning through the Sustainable Rangeland Management Project to protect shared grazing lands for livestock keepers in four clusters of villages covering 150,000 hectares. This led to adoption of the approach by the Government of Tanzania, including a new Global Environment Facility grant to expand joint village land use planning in five districts.